Efficiency estimation of the agromorphological traits in kernel weight development in landraces of rice - Chakravorty, Ashim; Ghosh, P.D (Current Botany, 2013)
The objective of this study was to estimate the efficiency of eighteen agromorphological traits, and to determine their interrelationships and their influence on kernel weight development in fifty one traditional rice cultivars. The experiment was conducted at Zonal Adaptive Research Station, Krishnagar, Nadia, West Bengal, following Randomized Complete Block Design with two replications during kharif season of 2008, 2009 and 2010. In maximum cases, the genotypic correlations were higher than the phenotypic correlations. Results of correlation analysis cited that traits, such as, grain weight (0.988), grain length (0.508), grain breadth (0.292) correlated significantly and positively with kernel weight and positively with leaf length (0.258) and flag leaf angle (0.292) Path coefficient analysis revealed that grain weight having maximum direct effect (0.999) on kernel weight is followed by number of grains panicle-1(0.212), leaf length (0.112) and grain length/breadth ratio (0.108). Hence, the study showed that the direct selection of the above said traits could be relied upon for selection of genotypes for crop improvement as the traits revealed positive relationship with the kernel weight development.